KEMAMPUAN MENENTUKAN CITRAAN PUISI KARYA SAPARDI DJOKO DAMONO PADA SISWA SMP - Kartika Rahayu Effendi; Mulyanto Widodo; Ni Nyoman Wetty Suliani (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2013)
Problem in this research is how to determine the imagery of the poem by Sapardi Djoko Damono in student at class VIII SMP. with the aim to describe the ability of students to determine imagery poem. Methods used in research is descriptive method. The population in study are all students of class VIII  SMP which amounts 168 people. Sample is taken is 20, so the total sample is 33 students. Data collecting techniques used was technical test with question test is  20 multiple choice and 2 essay questions. After the data is analysed obtained the score after as follows. The ability determine imagery poem of multiple choice questions with indicator visual imagery  is 73 quite, indicator auditory imagery is sufficient 74,  indicator termal imagery is 66 classified as sufficient, indicator kinestetik imagery was 67 classified sufficient,  Indicator olfactory imagery is 68 was sufficient. The ability to understand the essay question with indicator explain the definition imaging poetry is 86 classified very well. Indicators explain and mention the types of imagery with other names is 63 classified sufficient.Kata kunci: citraan, kategori, kemampuan pencitraan puisi